Single-Cell Transcriptomic Dataset of RPGR-associated Retinitis Pigmentosa Patient-Derived Retinal Organoids - Ting Li; Yuting Ma; Yun Cheng; Yingke Zhao; Zhixu Qiu; Hongli Liu; Daowei Zhang; Jiawen Wu; Junfeng Li; Shenghai Zhang; Jihong Wu (Scientific Data)
Abstract X-linked retinitis pigmentosa (XLRP) is a severe hereditary retinal disorder marked by progressive vision loss due to photoreceptor dysfunction. The retinitis pigmentosa GTPase regulator (RPGR) gene, responsible for most XLRP cases, encodes a protein crucial for the transport of visual signal proteins between the photoreceptor inner and outer segments. However, the mechanism of RPGR mutation causing photoreceptor disorder is not clear and effective treatments remain elusive. This study utilized retinal organoids (ROs) derived from normal and RPGR-mutant human induced pluripotent stem cells (hiPSC) at four developmental stages (40, 90, 150, and 200 days). Single-cell RNA sequencing (scRNA-seq) was conducted on 71,096 cells, including 33,839 cells from the control group and 37,257 cells from the RPGR group. Key retinal cell types were identified and the obtained scRNAseq dataset was validated reliable and high -quality. This study has provided data resources and references for exploring the mechanism of RPGR-related retinal degeneration and support the development of targeted therapies.